Powinności w perspektywie kategorii znikomej szkodliwości czynu – spojrzenie praktyka – prokuratora konstytucjonalisty. - Stankowski, Andrzej (Kwartalnik Prawa Publicznego, 2016)
The Constitution of the Republic of Poland of 2 April 1997 lays down – in Art. 42 sec. 1 – the principle that criminal liability is incurred for a criminal offense by a statute in force at the time of its committal, but it does not formally impose liability on the charge of the social detriment of the act. However, in Polish penal law, a standard has been in place for a long time to correct this type of liability based on the assessment of the material substrate of the act – in accordance with Art. 1 item. 2 of the applicable Criminal Code, if a social harm is negligible, it does not constitute a criminal offense. This kind of correction is justified by the judicial case law. The assessment of the social detriment of the act in concreto finds its axiological justification in the Constitution of the Republic of Poland, despite the fact there is no mention of a rule expressing such standard in basic law. Truth and justice are constitutional values, and these values require that any action that is in breach of the applicable rules of conduct be truly described and justified. At the same time, it should be emphasized that, in this process, legislative bodies should retain a large margin of liberty. After all, the final assessment in this matter will be made by an independent court and the independent judge that rules in its name.